FUNGSI PENGAWASAN DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KABUPATEN BENGKAYANG DALAM PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA - Heliana E.42009047 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
This Thesis aims to reveal the function of monitoring the implementation of the social services workforce and transmigration Bengkayang Regency and analyze the factors that affect to function of supervision.Research conducted a descriptive research with a qualitative approach.Result of this study indicate that the oversight function performed by the social services workforce and transmigration is not optimal due to several internal and external factors affecting the placement and protection of workeds in the country and abroad. Internal oversight is supervision conducted by the department head of the employee’s performance in carrying out the duties and functions. Internal monitoring is  not optimal due to several other factors, including turnover and placement that are not appropriate according to skills and education. External oversight by an employee according to their respective areas of society. Some factors affecting the external oversight is the lack of awareness among worker in the social services report to the manpower and transmigration, at least the company reports that will be difficult to control and the protection of employees in workplace safety. Reports are created automatically will give legal force to the labor. Keywords : Oversight Function, Social Service Manpower and Transmigration,Placement and Labor Protection, Internal Oversight, External Oversight